CORRELATION DYNAMICS OF ERRORS AND COMPLICATIONS IN THE USE OF RESTORATIVE POST CONSTRUCTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Restoration of dental hard tissue defects is one of the actual problems of orthopedic dentistry. Restoration of destroyed teeth using endocanal posts has always been one of the fundamental problems of dentistry. The choice of the type and determination of the number of posts depends on the volume and patency of the canal after endodontic treatment, the number of root canals, the loss of dentin mass, the distance to antagonist teeth and neighboring teeth.